(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In the article ,the great scientist Pestalozzi’s contributions to the field of pedagogy, his works on the field of education and pedagogy and his scientific views are written In addition, the efforts made to save the people from tyranny are discussed.